2009
DOI: 10.1111/j.1582-4934.2008.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel histone deacetylase inhibitor prevents IL‐1β induced metabolic dysfunction in pancreatic β‐cells

Abstract: The histone deacetylase (HDAC) inhibitor trichostatin A (TSA) has recently been shown to inhibit deleterious effects of cytokines on β‐cells, but it is unable to protect β‐cells from death due to its own cytotoxicity. Herein, we investigated novel HDAC inhibitors for their cytoprotective effects against IL‐1β‐induced damage to isolated β‐cells. We report that three novel compounds (THS‐73–44, THS‐72–5 and THS‐78–5) significantly inhibited HDAC activity and increased the acetylation of histone H4 in isolated β‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…We recently reported that the KDAC inhibitors SAHA and trichostatin A markedly reduced cytokine-induced beta cell functional failure and death in vitro, a finding confirmed by others [12,25,42]. Here we show that ITF2357 abrogated beta cell toxicity as measured by iNOS levels, nitric oxide formation, cleavage of caspase-3 and apoptosis, and reduced cytokine-mediated suppression of accumulated insulin release, in line with the previous studies.…”
Section: Discussionsupporting
confidence: 79%
“…We recently reported that the KDAC inhibitors SAHA and trichostatin A markedly reduced cytokine-induced beta cell functional failure and death in vitro, a finding confirmed by others [12,25,42]. Here we show that ITF2357 abrogated beta cell toxicity as measured by iNOS levels, nitric oxide formation, cleavage of caspase-3 and apoptosis, and reduced cytokine-mediated suppression of accumulated insulin release, in line with the previous studies.…”
Section: Discussionsupporting
confidence: 79%
“…These compounds further exerted no toxic effects on metabolic cell viability in these cells. However, among the three compounds tested only 94 protected against IL-1β-mediated loss in β-cell viability 160. Remarkably, compound 94 differs from 96 , which does not protect against this loss in β-cell viability, by a single carbon in the linker chain region.…”
Section: Polyamine-based Histone Deacetylase (Hdac) Inhibitorsmentioning
confidence: 93%
“…Immune stimuli together with the induction of lipotoxicity induce β‐cell apoptosis and dysfunction in pancreatic islets 49 . KDAC inhibitors promote β‐cell function including development, proliferation and differentiation in animal models of diabetes and insulin resistance 49 , 50 , 51 . In isolated β‐cells, KDAC inhibitors increased the acetylation of histone H4 and inhibited KDAC activity without any toxic responses 50 .…”
Section: Pancreasmentioning
confidence: 99%
“…KDAC inhibitors promote β‐cell function including development, proliferation and differentiation in animal models of diabetes and insulin resistance 49 , 50 , 51 . In isolated β‐cells, KDAC inhibitors increased the acetylation of histone H4 and inhibited KDAC activity without any toxic responses 50 . In IL‐1β induced β‐cell dysfunction, KDAC inhibitors attenuated increased expression of inducible NO synthase and NO release, attributed to preventing IL‐1β activation of NFκB.…”
Section: Pancreasmentioning
confidence: 99%
See 1 more Smart Citation